Profile of an occupation – hotel management clerk - Schambeck, Arne [Verfasser] (My University, 2023)
"The hospitality sector was badly shaken up during the coronavirus pandemic. Modernisation of the hotel occupations thus occurred at the right time. The training occupation of hotel management clerk addresses many of the changes that have taken place in the sector and now offers business management aspects and further main focuses in the areas of HR and commercial management." (author's abstract; BIBB-Doku)
Keywords: G 1.2.4.2.3 Gastgewerbe; S 6.4.7.1 Gästebetreuer; 370; Kaufmann für Hotelmanagement; Berufsbild; Neuordnung der Ausbildungsberufe; Berufschance